The Unknown Narrators in MusnadIbn al-Ja'd: Some Selected Examples (Collection and Study) - Kahlan Hassan Ali, (Islamic Sciences Journal, 2025)
ABSTRACT It is no secret to people of knowledge and insight that the Sunnah is the second source of legislation after the Glorious Qur'an. It explains it, restricts its absolute meanings, and specifies its generalities. Therefore, our righteous predecessors paid attention to it throughout every era, generation after generation, until it reached us, preserved in our hearts and in our writings, with chains of transmission and texts. This is a characteristic for which our nation is known, unlike any other. No nation has preserved the traces of its Prophet like ours. Part of this attention was to identify the obscure narrators in the Musnad of Ibn al-Ja'd - the Musnad of the Tribes - by collecting the chains of transmission of each of these hadiths in which there was ambiguity, in order to arrive at the name of the obscure narrator.